D’ Merah Pastry Cafe Project: The marketability of Students with Special Needs (SEN) in Pastry Basic Skills as a Career Transition - Wan Abdul Jalil, Wan Norafadila; Rahman, Rezzlin Abdul (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The transition to career at secondary schools has been implemented according to the improved SEN Transition Model guideline. This implementation encompasses the fields of skills perceived as one of the students’ marketability channels in career transition. Thus, students with special education needs of the medium function are trained in pastry-making skills as one of the branches that can provide bright opportunity and future for them. Pastry-making is seen as the best medium for them to embark upon a higher level in their career. However, the difficulty in getting a place in the community is due to the absence of specific certification, leading to the SEN’s difficulty to be marketed in the community. Employer’s trust is also the main reason for the non-marketability of the students in the industry. A study is conducted involving a private collaboration between D’ Merah Pastry Cafe and A 9 Legacy Enterprise as the SEN’s temporary employer to realize the idea of “café simulation”, where students with special needs are able to work at school as they would in the real industry. The overall finding of the qualitative study involving five parents of the students working in the café, one representative from the private agency and three teachers or regular customers of the café not only helped to ascertain the effectiveness of the project, but also prepared a basic model of the transition career that can be followed by other schools. The encouragement from trainers, the support given by the private agency and the facility that contributed to the positive outcome of the transition career have given some relevant impact to the Students with Special Needs.